In vitro and in vivo uptake of azithromycin (CP-62,993) by phagocytic cells: possible mechanism of delivery and release at sites of infection. - Gladue, R P (1989)
Azithromycin, a novel azalide antibiotic, concentrated in human and mouse polymorphonuclear leukocytes (PMNs), murine peritoneal macrophages, and mouse and rat alveolar macrophages, attaining intracellular concentrations up to 226 times the external concentration in vitro. In murine peritoneal macrophages, azithromycin achieved concentration gradients (internal to external) up to 26 times higher than erythromycin. The cellular uptake of azithromycin was dependent on temperature, viability, and pH and was decreased by 2,4-dinitrophenol. Azithromycin did not decrease phagocyte-mediated bactericidal activity or affect PMN or macrophage oxidative burst activity (H2O2 release or Nitro Blue Tetrazolium reduction, respectively). Azithromycin remained in cells for several hours, even after extracellular drug was removed. However, its release was significantly enhanced by phagocytosis of Staphylococcus aureus (82 versus 23% by 1.5 h). In vivo, 0.05 micrograms of azithromycin was found in peritoneal fluids of mice 20 h after oral treatment with a dose of 50 mg/kg. Following caseinate-induced PMN infiltration, there was a sixfold increase in peritoneal cavity azithromycin to 0.32 micrograms, most of which was intracellular. Therefore, the uptake, transport, and later release of azithromycin by these cells demonstrate that phagocytes may deliver active drug to sites of infection.